2020
DOI: 10.3390/ani10020200
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Carcass and Meat from Geese Fed Diets with or without Soybean Meal

Abstract: The aim of the study was to compare the carcass and meat quality of geese fed with soybean meal or yellow lupin. In total, 210 White Kołuda® geese were divided into 2 groups (1, soybean meal (SBM); 2, yellow lupin (YL), potato protein, and brewer’s yeast) of 5 replications (21 birds per each). After 16 weeks, 10 geese (5 females, 5 males) from each group were slaughtered. Carcass dissection was done, and major physicochemical traits were analysed (pH, water holding capacity, drip loss, color, and chemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…The lack of significant differences in lightness (L*), redness (a*), and yellowness (b*) in the breast muscles and leg muscles in our own research indicates no differences in the structure of goose muscles in each group. Biesek et al [20] showed that the color of breast and leg muscles, as well as the chemical composition of muscles, were similar to our results. It could indicate that legumes have the same effect, or that the genotype of geese, which is White Kołuda ® geese, gave the described results.…”
Section: Physicochemical Traitssupporting
confidence: 91%
See 2 more Smart Citations
“…The lack of significant differences in lightness (L*), redness (a*), and yellowness (b*) in the breast muscles and leg muscles in our own research indicates no differences in the structure of goose muscles in each group. Biesek et al [20] showed that the color of breast and leg muscles, as well as the chemical composition of muscles, were similar to our results. It could indicate that legumes have the same effect, or that the genotype of geese, which is White Kołuda ® geese, gave the described results.…”
Section: Physicochemical Traitssupporting
confidence: 91%
“…The diet with the inclusion of white lupin increased the content of fat in breast and leg muscles. Similarly, Biesek et al [20] did not find a negative effect on most carcass traits, excluding leg muscles and their percentage content in carcasses. However, the values of the obtained results in the cited research were higher.…”
Section: Carcass Traitsmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast recently, Li et al [35] reported that using dietary cassava foliage as high protein content for Hainan China geese significantly (p < 0.05) decreased the level of pH 24 postmortem. The present study showed that moderate M + C gave the highest value of pH 24, which linked with meat quality as reported by Biesek, et al [36] who clarified that higher pH of goose meat is often associated with a higher water-holding capacity. On the other hand, the protein percentage of breast muscle significantly (p < 0.01) increased with increasing dietary levels of crude protein.…”
Section: Meat Compositionsupporting
confidence: 86%
“…Nevertheless, increasing soybean prices prompted researchers to investigate other sources of protein suitable for animal diets 8 . Biesek et al 9 concluded that legumes, particularly lupin seeds, are a promising source of protein for poultry diets, although they do not provide sufficient amounts of starch or easily digestible carbohydrates. In the past, the use of legume seeds was limited because of their high content of antinutrients, despite the fact that lupins, depending on the cultivar, contain approx.…”
Section: Introductionmentioning
confidence: 99%